Iowa RBA, March 10, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for March 10, 1997. Highlights of the update include many new arrivals to the state, including American White Pelicans, Turkey Vultures, and an Eastern Phoebe. Also of note was the continued presence of at least one Great Gray Owl and an immature Pinyon Jay as well as the observation of a first-year Thayer's Gull. Also included are handwritten notes for the next week's update with sightings of American Woodcocks and a Sandhill Crane. Epson - sheet feed/flatbed